The primacy of semantic comments in Xitsonga/English dikixinari/dictionary : a lexicographic analysis - Hosana, Nxalati Angellah (My University, 2010)
Some dictionaries are presented in such a way that their target users could not easily retrieve the required semantic information with special reference to Xitsonga/English Dikixinari/Dictionary (2005). Semantic information in the dictionary is presented unsystematically. In some cases extra-linguistic information in the form of contextual guidance is presented, which is regarded as secondary information in the place of semantic information (which is primary). The study evaluates this dictionary in terms of the primary of semantic comments in Xitsonga/English Dictionary. The study finds that translation equivalents are not arranged systematically in the microstructure. The research concludes that extra-linguistic information in a form of contextual guidance must be systematical used in the microstructure of Xitsonga/English Dikixinary/Dictionary (2005) so that dictionary users could be able to retrieve systematic information that could help them to speak the target language in a communicative functional way. This as a result will lead to communicative success.
Thesis (M.Ed.) --University of Limpopo, 2009.
Keywords: lexicographic analysis; microstructure; Xitsonga dictionary; translation equivalents; semantic comment